The Role of Digital Financial Services on Indian MSMEs - Gupta, Upasana; Agarwal, Bhawna (Indian Journal of Finance, 2023)
Purpose : This paper aimed to examine the role of digital financial services on registered micro, small, and medium enterprises in India. This study examined the MSME knowledge, usage, and preferences about several digital financial technologies. Further, the paper discussed the impact of demographic variables on DFS adoption. Methodology : Primary data were gathered for the study. The questionnaire had three parts. The first part covered demographic variables. The second part identified questions related to DFS awareness and the reason for adopting DFS. The last part covered DFS adoption in various financial activities. Findings : DFS awareness in the MSME sector was high but far from the required level. Demonetization and COVID-19 also increased the awareness of DFS in the Indian MSME sector. The DFS adoption was found to be affected by the age and experience of the owner/manager. Also, the educational level of the owner/manager did not always impact the DFS adoption. Practical Implications : Digital financial service providers should increase customer satisfaction and reduce administrative expenses by making their website or application user-friendly to attract MSMEs. Additional government support is essential to enhance DFS awareness among MSMEs. Originality/Value : This study added to the limited existing literature on MSMEs and their knowledge of digital payments.